Method and system for measuring anisotropic thermal conductivity of small-size single crystal sample

By using epoxy resin curing agent and polishing technology to expose different crystal surfaces on small-sized single crystal samples, and measuring thermal conductivity in combination with time-domain thermal reflection method, the problems of poor thermal contact and measurement error in traditional methods are solved, achieving high Accurate anisotropic thermal conductivity measurement, suitable for thin films and single crystal materials with larger thickness.

CN119269576APending Publication Date: 2025-01-07NANJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411529015.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Traditional thermal conductivity measurement methods have problems such as poor thermal contact, insufficient stability and measurement errors when measuring small single crystal samples, making it difficult to accurately measure their anisotropic thermal conductivity, especially in thin films or single crystal materials with larger thickness. middle.

Method used

By fixing multiple samples perpendicularly in the mold with different crystal plane orientations, the sample is fixed using a mixed curing agent of epoxy resin and hardener, and graded polishing is performed to expose the crystal planes in different directions, and measurement is combined with the time domain heat reflection method. In-plane and out-of-plane thermal conductivity ensures measurement accuracy and stability.

Benefits of technology

Improves the stability and accuracy of the anisotropic thermal conductivity measurement of small-sized single crystal samples, reduces the impact of roughness on measurement results, is suitable for thin films and single crystal materials with thicknesses greater than 50μm, and simplifies sample preparation and measurement. Steps, which reduce experiment time and cost, provide reliable data support.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119269576A_ABST
    Figure CN119269576A_ABST
Patent Text Reader

Abstract

The invention discloses a method and a system for measuring anisotropic thermal conductivity of a small-size single crystal sample, and the method comprises the following steps: providing a film sample or a small-size single crystal material sample of which the thickness is greater than 50 microns, and vertically fixing a plurality of samples in a mold in different crystal face orientations; the sample is polished, so that the crystal faces exposed in different directions are all polished and ground, and the crystal faces in different orientations are all exposed; the anisotropic thermal conductivity of the material is calculated by measuring the in-plane thermal conductivity and the out-of-plane thermal conductivity of the sample. The system comprises a mold for fixing a sample, a polishing machine for performing graded polishing on the sample, and a thermal conductivity measuring instrument for measuring the in-plane and out-plane thermal conductivity of the sample. According to the measurement method disclosed by the invention, a plurality of samples are respectively fixed in different crystal face orientations, a certain interface is intercepted during polishing, and crystal faces in different orientations of all the samples can be exposed at the moment, so that the crystal faces exposed in different directions are obtained, and the measurement of the anisotropic thermal conductivity is more accurate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method and a system for measuring the anisotropic thermal conductivity of a material, and in particular to a method and a system for measuring the anisotropic thermal conductivity of a small-sized single crystal sample. Background Art

[0002] In modern materials science, the measurement of anisotropic thermal conductivity is crucial for understanding and optimizing material properties. Many small-sized single-crystalline materials, especially layered oxides, exhibit significant anisotropy, that is, their thermal conductivity varies in different directions. This anisotropy not only affects the thermal management performance of the material, but also has an important impact on its performance in electronic devices, thermoelectric materials and other high-performance applications.

[0003] In the context of the rapid development of microelectronics and nanotechnology, traditional thermal conductivity measurement methods are often unable to effectively solve problems such as poor thermal contact, insufficient stability, and measurement errors when facing small-sized single crystal samples. In addition, the characteristics of small-sized samples make the anisotropic characteristics of their thermal conductivity more obvious, which directly affects the heat dissipation capacity and work efficiency of the material. Therefore, accurately measuring the anisotropic thermal conductivity of small-sized single crystal materials is not only an important part of basic research, but also a necessary condition for promoting the development and application of new materials.

[0004] In terms of thermal conductivity measurement technology, commonly used methods include microbridge method, hot wire method, laser pulse method and time domain thermoreflectance spectroscopy (TDTR) method. However, these methods may face problems such as insufficient measurement accuracy or complex sample processing in some cases.

[0005] Therefore, it is particularly important to develop an efficient and accurate thermal conductivity measurement technology, especially for the in-plane thermal conductivity measurement of thin films or single crystal materials with large thickness (greater than 50μm). Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a method for measuring anisotropic thermal conductivity of small-sized single crystal samples that can improve measurement stability and accuracy;

[0007] A second object of the present invention is to provide a system used in the above method.

[0008] Technical solution: The method for measuring anisotropic thermal conductivity of a small-sized single crystal sample of the present invention comprises the following steps:

[0009] (1) Provide thin film samples or small-sized single crystal material samples;

[0010] (2) fixing multiple samples vertically in a mold with different crystal plane orientations;

[0011] (3) polishing the sample so that the crystal planes exposed in different directions are polished and polished, thereby exposing the crystal planes with different orientations;

[0012] (4) By measuring the in-plane thermal conductivity and out-of-plane thermal conductivity of the sample, the anisotropic thermal conductivity of the material is calculated.

[0013] Wherein, in step (1), the thickness of the thin film sample is greater than 50 μm; and the sample is a layered oxide material.

[0014] Among them, in step (2), firstly, a plurality of samples are vertically pasted to the bottom surface of the mold with different crystal plane orientations, and then a curing agent is poured into the mold so that the samples are fixed in the mold by the curing agent.

[0015] After the sample is fixed by the curing agent, the sample and the curing agent are taken out as a whole and polished.

[0016] Wherein, the curing agent includes epoxy resin and hardener; the mixing ratio of the epoxy resin and the hardener is a mass ratio of epoxy resin to hardener of 2.5:1-3.5:1. When the mixing ratio is close to 2.5:1, the hardness of the epoxy resin during the curing process may be relatively low, but the flexibility will increase, which may be more suitable in some application scenarios that require flexibility. When the mixing ratio is close to 3.5:1, the cured epoxy resin will be harder and more durable, but may be relatively brittle. This ratio is suitable for situations where higher strength and wear resistance are required.

[0017] Wherein, the epoxy resin is an epoxy resin containing aliphatic amine or aromatic amine.

[0018] Wherein, in step (3), a polishing machine is used to perform polishing with different grain sizes at least twice to obtain a smooth sample surface. The sample is irregularly oriented when pasted, and after polishing, crystal planes exposed in different directions can be obtained to perform anisotropic thermal conductivity measurement.

[0019] Among them, the coarse grain size is between tens of microns and hundreds of microns, and the fine grain size is usually between a few microns and tens of microns. Coarse grain polishing is mainly to remove large flaws and uneven parts on the sample surface, laying the foundation for subsequent fine grain polishing; the coarse grain size is between tens of microns and hundreds of microns. Fine grain polishing is to further improve the flatness and smoothness of the sample surface on the basis of coarse grain polishing to meet the requirements of thermal conductivity measurement; the fine grain polishing particle size is usually between a few microns and tens of microns.

[0020] In step (4), the in-plane and out-of-plane thermal conductivities are measured using the time domain thermal reflectance method; the temperature change of the sample is monitored during the measurement process to ensure the measurement accuracy. After the measurement, the measurement results are compared with those of the Raman spectroscopy method or the thermal bridge method to verify the effectiveness of the method.

[0021] The system used in the above method includes a mold for fixing a sample, a polishing machine for graded polishing of the sample, and a thermal conductivity measuring instrument for measuring the in-plane and out-of-plane thermal conductivities of the sample.

[0022] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:

[0023] (1) The measurement method of the present invention fixes multiple samples with different crystal plane orientations, and intercepts a certain interface during polishing. At this time, the crystal planes of all samples with different orientations can be exposed, and crystal planes exposed in different directions are obtained, so that the anisotropic thermal conductivity measurement is more accurate. (2) The present invention processes the sample by mechanical polishing to ensure that its surface is flat, thereby effectively reducing the influence of roughness on the thermal conductivity measurement results. Combined with TDTR technology, high-precision in-plane thermal conductivity data can be obtained to reflect the true thermal conductivity characteristics of the material. (3) The present invention is suitable for a variety of layered materials, especially thin films and single crystals with a thickness greater than 50μm, to meet the needs of modern material research for in-plane thermal conductivity measurement of different types of materials. (4) Traditional thermal conductivity measurement methods have problems such as poor thermal contact and environmental impact in layered materials. The present invention effectively improves these problems through epoxy resin fixation and mechanical polishing, ensuring the stability and accuracy of the measurement process. (5) The present invention simplifies the sample preparation and measurement steps, which can effectively reduce experimental time and labor costs and improve experimental efficiency. (6) The measurement results show good consistency compared with other traditional methods, further verifying the effectiveness of this method in in-plane thermal conductivity measurement; this provides researchers with reliable data support and helps to deeply analyze material properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a flow chart of the method of the present invention;

[0025] Figure 2 A schematic diagram of the structure of the device used in the method of the present invention;

[0026] Figure 3 for Figure 2 Schematic diagram of the structure of single crystal samples with different crystal planes exposed after mechanical polishing;

[0027] Figure 4 for Figure 2 The top view of the single crystal sample with different crystal planes exposed after mechanical polishing;

[0028] Figure 5 It is a schematic diagram of the arrangement and crystal surface structure of a small-sized single crystal sample of the present invention;

[0029] Figure 6 The Bi measured by the present invention2 O 2 The relationship between the out-of-plane and in-plane thermal conductivity of Se single crystal and temperature. DETAILED DESCRIPTION

[0030] The present invention is described in further detail below.

[0031] like Figure 1 As shown, the present invention provides a method for measuring the anisotropic thermal conductivity of a single crystal sample of a certain size, and the system used in the method is as follows Figure 2 As shown, it includes: a mold 1 for fixing a sample 2, a polishing machine 5 for graded polishing of the sample 2, and a thermal conductivity measuring instrument (not shown in the figure) for measuring the in-plane and out-of-plane thermal conductivity of the sample 2. The method specifically includes the following steps:

[0032] 1. Material preparation

[0033] Choose high quality Bi 2 O 2 Se single crystal material, ensure that the sample thickness is greater than 50μm. This thickness range can effectively avoid edge effects and inhomogeneities that may occur during the measurement process; Figure 2 , 3 In the figure, a small cuboid represents an irregular single crystal;

[0034] The epoxy resin 4 and the hardener are mixed in a ratio of 3:1, wherein the hardener is aliphatic amine or aromatic amine. This ratio can ensure good adhesion and stability of the epoxy resin 4 during the curing process.

[0035] Polishing materials: Prepare polishing pads and polishing liquids of different particle sizes for graded polishing of samples.

[0036] 2. Sample pasting

[0037] During the sample pasting stage, first ensure that Bi 2 O 2 The surface of the Se single crystal sample is clean, free of dust and impurities. Then apply double-sided tape 3 evenly on the bottom surface of sample 2, and paste it vertically on the bottom surface of mold 1, so that each single crystal sample 2 presents a different crystal plane orientation. When pasting, the samples need to be pasted and placed in various positions to expose the various crystal planes of the samples that need to be measured as much as possible. When pasting, paste the sample 2 according to the required crystal plane orientation. The following is an example of sample pasting: For example, if you need to measure Bi 2 O 2 Se crystal in-plane thermal conductivity, it is necessary to expose Bi 2 O 2 First, carefully observe the ab plane of the Se single crystal, that is, the in-plane 2 O 2Se single crystal sample, determine the characteristics of each crystal plane. Then, apply the double-sided tape evenly on the bottom surface of the sample to ensure that the viscosity of the double-sided tape is evenly distributed. Next, according to the characteristics of the ab crystal plane, the sample is vertically pasted on the bottom surface of the mold at a specific angle and direction. For example, one edge of the sample can be aligned with a reference line on the bottom surface of the mold so that the ab crystal plane can be exposed to the greatest extent. During the pasting process, press the sample gently to ensure that it is in full contact with the double-sided tape and firmly pasted. At the same time, care should be taken to avoid rotation or movement of the sample during the pasting process to ensure the accuracy of the crystal plane orientation. In this way, in the subsequent processing process, operations can be performed according to the predetermined crystal plane orientation to ensure the accuracy and reliability of the measurement results. This step ensures that the sample is firmly pasted to avoid displacement or loosening in subsequent processing.

[0038] 3. Epoxy resin pouring

[0039] After mixing the epoxy resin 4 and the hardener, stir them thoroughly to ensure that they are evenly mixed. Then, slowly pour the mixed epoxy resin 4 into the mold 1 to ensure that Bi 2 O 2 The Se single crystal sample is completely immersed in the epoxy resin 4. During this process, bubbles should be avoided as much as possible, and bubbles can be released by gently tapping the bottom of the mold 1. After the pouring is completed, the mold 1 is left at room temperature to allow the epoxy resin 4 to cure naturally, which usually takes 3 to 4 hours. During the curing process, severe vibration and temperature changes should be avoided to ensure the stability and strength of the epoxy resin 4.

[0040] 4. Sample removal

[0041] After the epoxy resin 4 is completely cured, the sample 2 wrapped in the epoxy resin 4 is removed from the mold 1 as a whole. At this point, the sample 2 should be firmly fixed in the epoxy resin 4 and the surface should be flat. A cutter can be used to gently cut off the excess part around the epoxy resin 4 to better remove the sample. The key to this step is to prevent damage to the sample surface.

[0042] 5. Sample polishing

[0043] After taking out the sample, use a high-precision polishing machine 5 for graded polishing. First, use a coarser polishing pad with a coarse grain size between tens of microns and hundreds of microns for preliminary polishing to remove the unevenness and defects on the sample surface. During polishing, uniform pressure and speed should be maintained to ensure the consistency of the polishing effect. Subsequently, gradually replace it with a polishing pad with a fine grain size between a few microns and tens of microns for detailed polishing. The time for each polishing should be controlled within 5 to 10 minutes, and the specific time can be adjusted according to the smoothness of the sample surface.

[0044] according to Figure 2 When grinding in the direction of the arrow, grind until Figure 2At the dotted line position in the figure, you will get crystal planes with various exposed orientations, because the sample has been pasted according to the required crystal plane orientation during pasting, such as Figure 3 As shown. By performing vertical time-domain thermal reflection thermal conductivity test from top to bottom, we can measure crystal planes with different orientations, some of which are in the c-axis direction, some in the ab-axis direction, that is, in-plane, out-of-plane; or inclined and other oriented crystal planes. The top view of the exposed surface of the sample after polishing is shown as follows Figure 4 As shown; the small-size single crystal sample arrangement and crystal surface structure stereogram are shown in Figure 5 shown.

[0045] After polishing, the surface of the sample is inspected using an optical microscope to ensure that the sample is fully exposed in all directions and that there are no obvious scratches and defects on the surface.

[0046] Since the sample has an irregular orientation when pasted, crystal planes exposed in different directions can be obtained after polishing to perform anisotropic thermal conductivity measurements.

[0047] 6. Thermal conductivity measurement

[0048] Place the polished sample on the test bench of the thermal conductivity measuring instrument to ensure good thermal contact between the sample and the measuring instrument. Thermal conductive paste can be used to enhance the thermal contact effect.

[0049] The in-plane thermal conductivity is measured using the time domain thermal reflectance method (TDTR). The specific steps are as follows: Apply a laser pulse to the sample surface to stimulate the temperature change on the sample surface. By detecting the time change of the reflected signal, the heat diffusion process is recorded and the in-plane thermal conductivity of the sample is calculated. At the same time, the out-of-plane thermal conductivity of the sample is measured using the same method to subsequently calculate the anisotropic thermal conductivity of the material.

[0050] 7. Data Analysis

[0051] Record the results of the in-plane and out-of-plane thermal conductivity measurements and perform a preliminary analysis. Calculate the in-plane thermal conductivity (K in ) and out-of-plane thermal conductivity (K out ) to determine the anisotropic thermal conductivity ratio of the material:

[0052]

[0053] The effectiveness of this method is verified by comparing the results with those of traditional measurement methods (such as Raman spectroscopy and thermal bridge method).

[0054] Figure 6 The Bi measured by the present invention 2 O 2 The relationship between the out-of-plane and in-plane thermal conductivity of Se single crystal and the temperature. Figure 6 It can be seen that Bi 2 O2 The in-plane thermal conductivity of Se single crystal at 300K is 1.23±0.15W m-1K-1, the out-of-plane thermal conductivity is 0.85±0.05W m-1K-1, and the anisotropy ratio is 1.45. The difference between in-plane and out-of-plane thermal conductivity provides ideas for further analysis of the transport mechanism, the atomic structure inside the material, and the influence of phonon behavior on the thermal conductivity of the material.

[0055] The result was compared with the measurement results of other methods, and the conclusions were consistent, which proved the effectiveness and reliability of the method of the present invention.

[0056] Conclusion: Through the above steps, the in-plane thermal conductivity of layered oxide single crystal materials was successfully measured. This method effectively solves many challenges encountered by traditional measurement techniques when dealing with layered materials, and provides reliable data support for materials science research. With the continuous development of new materials, the method of the present invention will play an important role in the research and application of thermoelectric materials, thermal barrier materials and other fields.

Claims

1. A method for measuring anisotropic thermal conductivity of a small-size single crystal sample, characterized in that: The following steps are involved: (1) Provide thin film samples or small-sized single crystal material samples; (2) fixing multiple samples vertically in a mold with different crystal plane orientations; (3) polishing the sample so that the crystal planes exposed in different directions are polished and polished, thereby exposing the crystal planes with different orientations; (4) By measuring the in-plane thermal conductivity and out-of-plane thermal conductivity of the sample, the anisotropic thermal conductivity of the material is calculated.

2. The method for measuring anisotropic thermal conductivity of a small-size single crystal sample according to claim 1, characterized in that: In step (3), a polishing machine is used to perform polishing at least twice with different grain sizes to obtain a smooth sample surface. The sample is irregularly oriented when pasted, and after polishing, crystal planes exposed in different directions can be obtained to perform anisotropic thermal conductivity measurement.

3. The method for measuring anisotropic thermal conductivity of a small-size single crystal sample according to claim 2, characterized in that: The coarse particle size is between tens of microns and hundreds of microns, and the fine particle size is usually between a few microns and tens of microns.

4. The method for measuring anisotropic thermal conductivity of a small-size single crystal sample according to claim 1, characterized in that: In step (2), a plurality of samples are firstly vertically attached to the bottom surface of the mold with different crystal plane orientations, and then a curing agent is poured into the mold so that the samples are fixed in the mold by the curing agent.

5. The method for measuring anisotropic thermal conductivity of a small-size single crystal sample according to claim 4, characterized in that: After the sample is fixed by the curing agent, the sample and the curing agent are taken out as a whole and polished.

6. The method for measuring anisotropic thermal conductivity of a small-size single crystal sample according to claim 4, characterized in that: The curing agent includes epoxy resin and hardener; the mass ratio of the epoxy resin to the hardener is 2.5:1-3.5:

1.

7. The method for measuring anisotropic thermal conductivity of a small-size single crystal sample according to claim 6, characterized in that: The epoxy resin is an epoxy resin containing aliphatic amine or aromatic amine.

8. The method for measuring anisotropic thermal conductivity of a small-size single crystal sample according to claim 1, characterized in that: In step (4), the in-plane and out-of-plane thermal conductivities are measured using a time-domain thermal reflection method.

9. The method for measuring anisotropic thermal conductivity of a small-size single crystal sample according to claim 1, characterized in that: In step (1), the film sample has a thickness greater than 50 μm; and the sample is a layered oxide material.

10. A system used in the method according to claim 1, characterized in that: The invention comprises a mold (1) for fixing a sample, a polishing machine (5) for graded polishing of the sample, and a thermal conductivity measuring instrument for measuring the in-plane and out-of-plane thermal conductivity of the sample.